THE ROLE OF DIGITAL TECHNOLOGIES IN TEACHING OF PHYSICS - Tusunboyev, Olmos (Физико-технологического образование, 2024)
In the article, the problem of digital technologies, the rapid development of the digital infrastructure of educational institutions, the training of personnel with modern digital competencies, the updating of specialties and educational fields taking into account the trends in the labor market, the formation of educational programs based on flexible educational trajectories, the development of the concept of continuous education, as well as , the processes of introduction of artificial intelligence systems in the educational environment are covered. Also, studies aimed at the introduction of digital technologies, which allow planning concrete steps to improve the educational system and change the work of educational institutions, have been carried out and suggestions have been formulated.